PHOSPHATE AND NITRATE DISTRIBUTION IN INNER AMBON BAY DURING NORTHWEST AND SOUTHEAST MONSOON - Idha Yulia Ikhsani; Malik Sudin Abdul; Johanis Dominggus Lekalette (Pusbindiklat - LIPI, 2016)
This study has compared the distribution of nutrients phosphate and nitrate concentrations in the inner Ambon Bay during two different seasons: Northwest and Southeast monsoon. The result showed that the nutrient concentrations in the Southeast monsoon were higher than those in the Northwest monsoon, both for phosphate and nitrate. The ranges of phosphate concentrations on the surface and near the bottom of the bay during the Northwest monsoon were 0.0471-0.0549 mg/L and 0.0549–0.1176 mg/L, while the ranges of nitrate concentrations were from undetected to 0.0976 mg/L on the surface, and 0.0956–0.5870 mg/L near the bottom of the bay. Meanwhile, the phosphate and nitrate concentration on the surface during the Southeast monsoon were 0.0495–0.0676 mg/L and 0.0247–0.4019 mg/L, while near the bottom the concentrations were 0.0495–0.1802 mg/L and 0.0247– 0.7944 mg/L. These results indicated that phosphate and nitrate concentrations in the inner Ambon Bay have exceeded the marine water standard quality, which can be categorized as polluted. High concentrations of phosphate and nitrate during Northwest monsoon could be caused by run-off from the mainland area that enters the bay trough the river. On the other hand, the enrichment of nutrients in the inner Ambon Bay during the Southeast monsoon could be dominated by the “nutrient-rich water mass” from Banda Sea that enters the inner Ambon Bay.